Development of an Algorithm for Experimental Evaluation of Increasing the Capacity of Mobile Telecommunication Networks (Texas Journal of Agriculture and Biological Sciences, 2023)
The article considers the average daily throughput of mobile telecommunication networks, one of the characteristics of which is the degree of workload of the system equipment during the day, which is estimated by the load concentration factor in the NNN. Also, an analysis was made of the features of managing user information flows in mobile networks, on a fragment of the LTE network